(untitled) (Research, Society and Development, 2024)
Alzheimer’s disease is a progressive neurodegenerative disorder that causes cognitive and memory interference and progressive impairment of daily activities. Epigenetic factors are related to the activation or suppression of pathological genes associated with Alzheimer’s. The present study aims to evaluate whether sleep duration shorter than recommended, as well as sleep quality, can increase the likelihood of developing Alzheimer’s disease in previously healthy adults and elderly people. This is an integrative literature review, carried out with the analysis of articles selected from the PubMed database, using the keywords Alzheimer, Sleep and Risk factors, verifying the research produced in the area in the last 5 years. Eight articles relevant to the research were found. Six demonstrate that sleep disorders are a risk factor for Alzheimer’s disease, which point to 7 to 9 hours of sleep as a protective factor for Alzheimer’s disease, while less than 5 hours of sleep or more than 30 minutes of sleep to fall asleep as a risk factor. Two articles highlight the change in sleep quality in advanced age as a pre-clinical phase of Alzheimer’s disease. Only one study, with a small sample, suggests that the average association between sleep duration and Aβ was not statistically significant. It is concluded that sleep deprivation may be a risk factor for the development of AD in advanced age, requiring further studies to prove it.